An unusual malposition of central venous catheter in critically ill patient. Could it be identified during catheterization? The potential role of point-of-care ultrasonography - Shrestha, Gentle Sunder; Poudyal, Bishesh Sharma (Bangladesh Critical Care Journal, 2016)
Malpositioning of central venous catheter is not uncommon and can be associated with complications. We report a case where central venous catheter inserted through right internal jugular approach under real time ultrasonographic guidance was malpositioned with its tip in left brachio-cephalic vein. Chest radiograph for detection of catheter malpositioning is associated with time delay and radiation exposure. Point-of-care ultrasonography can be a valuable bedside tool to identify catheter malpositioning during catheter insertion, thus facilitating immediate catheter repositioning and early use of central venous catheter. Bangladesh Crit Care J March 2016; 4 (1): 44-45